Humanized Mice as a Valuable Pre-Clinical Model for Cancer Immunotherapy Research - Cogels, Morgane M.; Rouas, Redouane; Ghanem, Ghanem E.; Martinive, Philippe; Awada, Ahmad; Van Gestel, Dirk; Krayem, Mohammad (Frontiers in Oncology, 2021)
Immunotherapy with checkpoint inhibitors opened new horizons in cancer treatment. Clinical trials for novel immunotherapies or unexplored combination regimens either need years of development or are simply impossible to perform like is the case in cancer patients with limited life expectancy. Thus, the need for preclinical models that rapidly and safely allow for a better understanding of underlying mechanisms, drug kinetics and toxicity leading to the selection of the best regimen to be translated into the clinic, is of high importance. Humanized mice that can bear both human immune system and human tumors, are increasingly used in recent preclinical immunotherapy studies and represent a remarkably unprecedented tool in this field. In this review, we describe, summarize, and discuss the recent advances of humanized mouse models used for cancer immunotherapy research and the challenges faced during their establishment. We also highlight the lack of preclinical studies using this model for radiotherapy-based research and argue that it can be a great asset to understand and answer many open questions around radiation therapy such as its presumed associated “abscopal effect”.